Three-Month-Old Infants Can Learn Task-Specific Patterns of Interlimb Coordination - Thelen, Esther (Psychological Science, 1994)
Three-month-old infants cannot yet coordinate and control their limbs for functional tasks like reaching or locomoting This study demonstrates that given an appropriate, novel task, infants can transform their seemingly spontaneous kicking movements into new and efficient patterns of interlimb coordination even at this early age Three-month-old infants were allowed to control the movement of an overhead mobile by means of a string attached to their left ankles In addition, some groups had their two legs yoked together at the ankle with a soft elastic The elastic permitted kicks to be coordinated in any pattern—alternating, single, or simultaneous—but simultaneous kicks provided the most vigorous activation of the mobile All infants kicked more and faster when their kicks were reinforced by mobile movement than when their kicks did not activate the mobile However, only the yoked infants increasingly moved their legs in a simultaneous, or in-phase, pattern The study suggests that learning processes are in place at 3 months for infants to discover a match between their interlimb coordination patterns and a specific task, and that these learning processes, rather than autonomous brain “maturation,” may underlie the acquisition of motor skills